Identification of Schistosoma mansoni eggs and other soil transmitted intestinal parasites in stool using Odongo-Aginya method - Byagamy, John Paul; Malinga, Geoffrey Maxwell; Angwech, Harriet; Echodu, Richard; Igwaro Odongo-Aginya, Emmanuel (Research Square, 2019)
Objective World Health Organisation recommends Kato-Katz technique for quantitative diagnosis of Schistosoma mansoni and other soil transmitted intestinal parasites in field research. However, for better visibility especially in hard stool specimens, the prepared slides in Kato-Katz technique are mostly examined after 1-2 hours. This longer clearing time over clear the eggs of parasites with thin cell walls in glycerine and morphology of the eggs are not often preserved in Kato-Katz method. These disadvantages are overcome using Odongo-Aginya method as illustrated by parasite eggs in the results. Result The Odongo-Aginya method uses compound stains of 7.5% nigrosin in 10% formalin and 0.5% eosin yellow in 10% formalin mixed 1:1 ratio. A drop of 50μl of the compound stain is added on 41.7mg of stool and stirred. This method illustrated the morphological appearance of S. mansoni and other soil transmitted intestinal parasites clearly when prepared and six weeks after preparation. The prepared slides maintained the morphological appearance including the eggs of hookworm after being kept in cool dry place for a long time. This method is reliable, reproducible, cost effective, easy to learn, quick and safe because of the base formalin, especially when handling specimens from Human Immunodeficiency virus infected patients.
Keywords: Odongo-Aginya method; Schistosoma mansoni; Intestinal parasites; Illustration in stool